2022
DOI: 10.1002/ente.202200059
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Novel Co2P/TiO2 Z‐Scheme Junction for Efficient Solar‐Driven Photocatalytic H2 Evolution

Abstract: Photocatalytic hydrogen production is a sustainable method to alleviate the energy crisis. Herein, the Co2P/TiO2 Z‐scheme junction photocatalysts without noble metal are synthesized by a simple hydrothermal method. Compared to pure TiO2 simple, the Co2P/TiO2 Z‐scheme junction photocatalysts exhibit much more excellent photocatalytic H2‐evolution activity, which suggests the Z‐scheme junction has a positive influence on the photocatalytic hydrogen production. Particularly, the optimal 3 wt% Co2P/TiO2 displays t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Moreover, to further study the reaction system of the catalyst, the effects of RuP 2 /Ti 4 P 6 O 23 @ TiO 2 -7 on hydrogen generation were compared to those of TiO 2 -based photocatalysts reported previously. [48][49][50][51][52] The RuP 2 / Ti 4 P 6 O 23 @TiO 2 -7 exhibits excellent photocatalytic hydrogen evolution capability (Table S1, ESI †). All the results indicated that RuP 2 / Ti 4 P 6 O 23 @TiO 2 -7 is a beneficial photocatalyst for the synchronous generation of hydrogen and lactic acid from an aqueous solution of biomass-derived feedstocks.…”
mentioning
confidence: 99%
“…Moreover, to further study the reaction system of the catalyst, the effects of RuP 2 /Ti 4 P 6 O 23 @ TiO 2 -7 on hydrogen generation were compared to those of TiO 2 -based photocatalysts reported previously. [48][49][50][51][52] The RuP 2 / Ti 4 P 6 O 23 @TiO 2 -7 exhibits excellent photocatalytic hydrogen evolution capability (Table S1, ESI †). All the results indicated that RuP 2 / Ti 4 P 6 O 23 @TiO 2 -7 is a beneficial photocatalyst for the synchronous generation of hydrogen and lactic acid from an aqueous solution of biomass-derived feedstocks.…”
mentioning
confidence: 99%